2018
DOI: 10.1098/rsob.180119
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the calcium feedback steps of vertebrate phototransduction

Abstract: We examined the genes encoding the proteins that mediate the Ca-feedback regulatory system in vertebrate rod and cone phototransduction. These proteins comprise four families: recoverin/visinin, the guanylyl cyclase activating proteins (GCAPs), the guanylyl cyclases (GCs) and the sodium/calcium-potassium exchangers (NCKXs). We identified a paralogon containing at least 36 phototransduction genes from at least fourteen families, including all four of the families involved in the Ca-feedback loop (recoverin/visi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 86 publications
(138 reference statements)
2
16
0
Order By: Relevance
“…Likewise, the distance from TRPC5 to GC-F (= GUCY2F) is <1 Mb in spotted gar ( Fig 6A) and <2.5 Mb in human ( Fig 6B); in the other 2 species, the loss of the gene for GC-F precludes this comparison (S8 Fig). Furthermore, as shown previously [30], in several cases members of the other 3 families of phototransduction genes are close to each other; for example, GRK1B, GC-E, and ARRB2 are close to each other in spotted gar (Fig 6A). Such proximity in extant chromosomes is an important telltale sign of ancient proximity because of the very low likelihood that random chromosomal rearrangements could bring so many genes into mutual proximity; instead, random rearrangements are likely to obscure any proximity that originally occurred.…”
Section: Plos Biologysupporting
confidence: 80%
“…Likewise, the distance from TRPC5 to GC-F (= GUCY2F) is <1 Mb in spotted gar ( Fig 6A) and <2.5 Mb in human ( Fig 6B); in the other 2 species, the loss of the gene for GC-F precludes this comparison (S8 Fig). Furthermore, as shown previously [30], in several cases members of the other 3 families of phototransduction genes are close to each other; for example, GRK1B, GC-E, and ARRB2 are close to each other in spotted gar (Fig 6A). Such proximity in extant chromosomes is an important telltale sign of ancient proximity because of the very low likelihood that random chromosomal rearrangements could bring so many genes into mutual proximity; instead, random rearrangements are likely to obscure any proximity that originally occurred.…”
Section: Plos Biologysupporting
confidence: 80%
“…Vertebrate species predating 2R WGD had one common ancestor of GC-D/E/F. The GC-E and GC-F/D split seems to have occurred before the vertebrate-specific WGD as studies in lamprey and hagfish have demonstrated ( Lamb and Hunt 2018 ). Initially, following a WGD event, the exon–intron structure of the duplicated genes is indistinguishable.…”
Section: Resultsmentioning
confidence: 97%
“…2016 ; Lamb and Kraft 2016 ; Lamb et al. 2018 ; Lamb and Hunt 2018 ). Nevertheless, the fate of phototransduction gene ohnologs in different vertebrate lineages following the 2R WGD has not been systematically investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like other family members, it contains four EF hand motifs and a myristoyl chain on the N-terminus. Only two of the EF hands (EF2 and EF3) bind Ca 2+ across species (Senin et al, 2002; Lamb and Hunt, 2018). Rcv undergoes a conformational change upon Ca 2+ binding in darkness and subsequently attaches to the disc membrane in photoreceptor outer segment (Tanaka et al, 1995; Ames et al, 1997).…”
Section: Introductionmentioning
confidence: 99%